Design and Analysis of Monopole Antenna Using Square Split Ring Resonator - S Salma, M C Rao, B Priyadharshini, B T P Madhav,D Ram Sandeep, B Charishma Nag, G Krishna Sai (International Journal of Advanced Science and Technology, 2020)
This paper presents a simple tri-band monopole antenna using a Square Split Ring Resonator (SSRR) for wireless communication devices. The projected antenna made of a single element and a split ring resonator with the distance between each split ring as 0.5λ0. For the broad area, the monopole antenna occupies a space of 36λ0×23λ0. This tri-band monopole antenna operates at resonances of 4.4, 5.8 and 8.6 GHz. The designed antenna offers Stable Gain and Radiation Patterns. Studied diversity gain (DG) parameter and the Mean Effective Gain (MEG) and presented in this work.